Multimedia Pembelajaran Pengenalan Tari Topeng Arsa Wijaya Berbasis Android - Gus Oka Ciptahadi, Ketut; Pasek Krisna A.S.J, IW; Bhaskara G, I Made (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya, 2023)
Topeng Arsa Wijaya dance is a dance that characterizes a king of Dalem as a king who holds the whip of government in the reign of the kingdom. The development of the topeng Arsa Wijaya dance is currently very rare, especially for teenagers. At schools such as SMA N 2 Amlapura, dance learning media is also limited to face-to-face and extracurricular, so it is difficult to introduce topeng Arsa Wijaya dance to students. Multimedia learning can be a solution to introduce dance and preserve Balinese culture, especially topeng Arsa Wijaya. The multimedia learning of topeng Arsa Wijaya's dance packaged in the Android operating system can make easier to introduce dance because it combines text, images, audio, video, and animation the information is more informative and interactive. This application is designed using the MDLC (Multimedia Development Life Cycle) method with Adobe Animate CC 2019 software using the ActionScript 3.0 programming language. Testing is done by black box testing and distributing questionnaires. Based on the implementation that has been done, it can be concluded that all buttons in the application are running well and the results of the questionnaire to 50 respondents get a score of 87.4% in the very good category.